Maytansinoids in cancer therapy: advancements in antibody–drug conjugates and nanotechnology-enhanced drug delivery systems - Matteo Perra; Ines Castangia; Matteo Aroffu; Federica Fulgheri; Rita Abi-Rached; Maria Letizia Manca; Hernán Cortés; María Luisa Del Prado-Audelo; Carla Nomura-Contreras; Alejandra Romero-Montero; Dietrich Büsselberg; Gerardo Leyva-Gómez; et al. (Discover Oncology)
Abstract Cancer remains the second leading cause of death globally, driving the need for innovative therapies. Among natural compounds, maytansinoids have shown significant promise, contributing to nearly 25% of recently approved anticancer drugs. Despite their potential, early clinical trials faced challenges due to severe side effects, prompting advancements in delivery systems such as antibody-maytansinoid conjugates (AMCs). This review highlights the anticancer activity of maytansinoids, with a focus on AMCs designed to target cancer cells specifically. Preclinical and clinical studies show that AMCs, including FDA-approved drugs like Kadcyla and Elahere, effectively inhibit tumor growth while reducing systemic toxicity. Key developments include improved synthesis methods, linker chemistry and payload design. Ongoing research aims to enhance the safety and efficacy of AMCs, integrate nanotechnology for drug delivery, and identify novel therapeutic targets. These advancements hold potential to transform maytansinoid-based cancer treatments in the future.